MENGUNGKAP KASUS KEKERASASAN SEKSUAL TERHADAP ANAK DENGAN BERMAIN - Sri Maslihah (MANASA, 2012)
Child sexual abuse was the highest among other child abuse in 2012. The research base on the handling of the case girl who became victim of sexual abuse by boy. The aim of the research is to explore the role of play as the method used in expressing the sexual assault case sexual abuse. This study is a qualitative research using a case study method. Techniques of data collection is observation. Result of this study show that through play activities obtained a description of sexual that occurs in the subject. In addition, the subject has the opportunity to express their feelings about the case.